PENGARUH MOTIVASI KERJA, DISIPLIN KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PALANG MERAH INDONESIA DI KOTA GEDE DAERAH ISTIMEWA YOGYAKARTA - Yohanes Ian Purwa Aditya; Prayekti Prayekti; Jajuk Herawati (Universitas Sarjanawiyata Tamansiswa, 2019)
The purpose of this study was to determine the effect of (1) Work Motivation on Employee Performance, (2) Work Discipline on Employee Performance, (3) Work environment for Employee Performance (4) jointly Work Motivation, Work Discipline, Work Environment, towards Performance of Indonesian Red Cross employees in Kotagede Special Region of Yogyakarta.Based on the relationship between variables on the object under study, this study is causal or called a causal relationship. population is the whole of the research subjects, namely the Indonesian Red Cross Employees in Kotagede Yogyakarta Special Region, amounting to 55 people, because less than 100 then the researchers took all employees, namely 55 employees as samples. Methods of collecting data with a questionnaire. While the technique of data analysis uses multiple regression analysis. Supported by hypothesis testing (T) and F test. And the classic assumption test consisting of Normality Test, Multicollinearity Test, and Heterocedasticity Test.The results of the data analysis with a significance of 0.05 indicate that Work Motivation has a significant positive effect on Employee Performance. Work Discipline has a significant positive effect on Employee Performance. The work environment has a significant positive effect on Employee Performance. There is a simultaneous influence of Work Motivation, Work Discipline and Work Environment variables that have significant positive Employee Performance.Keywords: Work Motivation (X1), Work Discipline (X2), Work Environment (X3), Employee Performance (Y)